Validation of Health Extension Workers Job Motivation Scale in Gamo-Gofa Zone, Southern Ethiopia: A Cross-Sectional Study. (24th February 2015) - Mohammed, Shikur; Tilahun, Marelign; Kote, Mesfin; Mama, Mohamedaman; Tamiru, Dessalegn
Abstract : Introduction. Well-trained and highly motivated community health workers are critical for delivery of community-based health care services. Understanding what motivates especially community health care providers for better community health requires the use of psychometrically reliable and valid scale. This study was conducted to validate job motivation scale in Gamo Gofa Zone, Southern Ethiopia. Methods. A cross-sectional study was conducted in 150 health care posts in Gamo Gofa Zone, from February 01, 2013, to March 01, 2013. A total of 301 participants responded to questionnaires asking about sociodemographic characteristics and job motivation. Exploratory factor analysis with principal component extraction and varimax with Kaiser Normalization rotation were employed to develop scales for job motivation. Eigenvalues greater than 1 were used as criterion of extraction. Items with item factor loadings less than 0.4 and double loaded items were dropped. Alpha and exploratory factor analyses were examined to test reliability and validity of the scale. Results. During exploratory factor analysis eight factors emerged from the three dimensions of job motivation scale, namely, educational career, workload, financial incentive, supervisor encouragement, community recognition, access to infrastructure, living condition, and better achievement in work. The factor loadings of the items in each dimension ranged from 0.58 to 0.83. Crobach's alpha of the scales ranged from 0.79 to 0.90. To check validities of the scales developed in this study, the previous studies conducted to develop job motivation scale were used. Conclusion. Although the present scale has the potential to measure the job motivation of health extension workers and it is low in cost and easy to administer and analyze, it should be field-tested at different settings.